The Role of Problem Representation Shifts in Auditor Decision Processes in Analytical Procedures - Bierstaker, James L.; Bedard, Jean C.; Biggs, Stanley F. (Auditing : a journal of practice and theory, 1999)
In audit analytical procedures, research has shown that auditors have difficulty proposing possible explanations for financial statement discrepancies (Bedard and Biggs 1991a). One source of this difficulty is that auditors may represent analytical procedures problems incorrectly; that is, their mental image of the problem does not contain the underlying cause of the discrepancies. Because shifting initial representations of problems is difficult, auditor decision processes are affected. The purpose of this study is to investigate how problem representation shifts can lead auditors to better insight into possible explanations of discrepancies, and thus improve auditor decision processes in analytical procedures. To accomplish this purpose, verbal protocol data from Bedard and Biggs (1991a) were used to develop a series of problem representations and prompts for the analytical procedures task used in that study. The prompts were given to activate relevant knowledge structures in memory and encourage successive shifts toward the correct representation. Think-aloud verbal protocols were collected from 12 senior auditors with three to five years' experience to provide evidence of problem representation shifts and decision processes. The results indicate that: (1) all subjects initially formulated an unproductive problem representation; (2) only one subject shifted to a productive problem representation and solved the case without prompts; and (3) even with prompts two subjects were unable to solve the case. These findings suggest that shifting to a productive problem representation was critical in achieving effective decision processes and identifying the seeded error in this analytical procedures task. Auditors who developed a thorough understanding of the financial relationships in the case prior to proposing potential solutions were better able to shift problem representations and solve the case. In addition, two processes related to an explanation inherited from client management, “wheel spinning” and truncated hypothesis generation, inhibited problem representation shifts.